Suprathel® for severe burns in the elderly: case report and review of the literature - Fischer, Sebastian; Kremer, Thomas; Horter, Johannes; Schaefer, Amelia; Ziegler, Benjamin; Kneser, Ulrich; Hirche, Christoph (Burns, 2016)
Large burns in aged patients are common and treatment often reveals challenging. Cardiovascular complications significantly contribute to the unfavorable prognosis in this group of high-risk patients. Pain medication and sedation can negatively influence cardiovascular stability. Suprathel® is well-known for its almost pain free application and reduction of dressing change intervals, and thus lowers the demand for potentially harmful analgesics and sedatives. We present the case of an 81-year-old patient with 51% of total burned body surface area (ABSI=12), who was completely treated with Suprathel®. Despite a predicted mortality of more than 80%, the patient survived and was discharged home without significant handicaps 69 days after burn. We hypothesize that Suprathel® beneficially contributed to the favorable clinical course of this critical patient as less frequent wound-dressing changes did not induce additional pain or sedative medication and thus improved cardiovascular stability.
Gesehen am 18.06.2020
Im Titel ist ® hochgestellt
This abstract was presented at the 34th Annual Meeting of the German Speaking Society for Burn Treatment in Berchtesgaden,Germany, 2016